Prognostic factors for acute posterior circulation cerebral infarction patients after endovascular mechanical thrombectomy: A retrospective study. Issue 17 (29th April 2022) - Gao, Jun; Wen, Changming; Sun, Jun; Chen, Di; Zhang, Donghuan; Wang, Ning; Liu, Yifeng; Wang, Jie; Zhang, Baochao
Abstract : Abstract: This article was to analyze the factors influencing the prognosis of posterior circulation cerebral infarction (PCCI) patients, retrospectively. One hundred forty five patients diagnosed with PCCI in Nanyang Central Hospital between June 25, 2016 and October 14, 2019 were included and underwent cerebral vascular mechanical thrombectomy. The clinical data of those patients were collected. The patients were followed up for 3 months to observe the prognostic efficacy and explore the influencing factors for poor prognosis. The potential prognostic factors for PCCI patients after emergency endovascular mechanical thrombectomy were analyzed by univariate and multivariable logistic regression. The thermodynamic diagram was drawn to explore the associations between the prognostic factors. The risk of poor prognosis in PCCI patients receiving emergency endovascular mechanical thrombectomy was reduced by 0.552 time with every 1-point increase of the Alberta Stroke Program Early CT in posterior circulation score (odds ratio [OR] = 0.448, 95% confidence interval [CI]: 0.276–0.727). The risk of poor prognosis was increased by 0.827 time for each additional grade in the digital subtraction angiography-American Society of Intervention and Therapeutic Neuroradiology grading (OR = 1.827, 95% CI: 1.221–2.733, P = .003) and increased by 0.288 time for every 1-point increase in National Institutes of Health Stroke scale at 24 hours (OR = 1.288, 95% CI: 1.161–1.429). All P < .05. Alberta Stroke Program Early CT in posterior circulation score, digital subtraction angiography-American Society of Intervention and Therapeutic Neuroradiology grading, National Institutes of Health Stroke scale score at 24 hours were factors affecting the prognosis of PCCI patients undergoing emergency endovascular mechanical thrombectomy, which might provide evidence for endovascular treatment of PCCI.